Torture and human rights in Northern Ireland: interrogation in depth - Duffy, Aoife (Routledge focus, 2019)
Introduction -- Background context -- Emergency regulations -- Internment 1971 -- Interrogation in depth -- Denial & concealment -- Conclusion.